The morphology of the pupae of six species of Philonthina (Coleoptera, Staphylinidae, Staphylinini) with taxonomic remarks - Pietrykowska-Tudruj, Ewa; Staniec, Bernard (Zootaxa, 2011)
The pupae of Bisnius fimetarius (Gravenhorst, 1802), Gabrius osseticus (Kolenati, 1846), Philonthus atratus (Gravenhorst, 1802), Philonthus carbonarius (Gravenhorst, 1802), and Philonthus debilis (Gravenhorst, 1802) are described and illustrated for the first time. The pupa of Philonthus decorus (Gravenhorst, 1802) is redescribed and illustrated. Some modifications of the generic diagnosis for Philonthus and Gabrius pupae are provided. The subtribal diagnostic morphological characters of the Philonthina are discussed.